Origin and Distribution of Thiophenes and Furans in Gas Discharges from Active Volcanoes and Geothermal Systems - Franco Tassi (International Journal of Molecular Sciences, 2010)
The composition of non-methane organic volatile compounds (VOCs) determined in 139 thermal gas discharges from 18 different geothermal and volcanic systems in Italy and Latin America, consists of C2–C20 species pertaining to the alkanes, alkenes, aromatics and O-, S- and N-bearing classes of compounds. Thiophenes and mono-aromatics, especially the methylated species, are strongly enriched in fluids emissions related to hydrothermal systems. Addition of hydrogen sulphide to dienes and electrophilic methylation involving halogenated radicals may be invoked for the formation of these species. On the contrary, the formation of furans, with the only exception of C4H8O, seems to be favoured at oxidizing conditions and relatively high temperatures, although mechanisms similar to those hypothesized for the production of thiophenes can be suggested. Such thermodynamic features are typical of fluid reservoirs feeding high-temperature thermal discharges of volcanoes characterised by strong degassing activity, which are likely affected by conspicuous contribution from a magmatic source. The composition of heteroaromatics in fluids naturally discharged from active volcanoes and geothermal areas can then be considered largely dependent on the interplay between hydrothermal vs. magmatic contributions. This implies that they can be used as useful geochemical tools to be successfully applied in both volcanic monitoring and geothermal prospection.